Development of phase change eco-composite materials from eggshell waste - Wafa Ben Aribia; Abdelwaheb Trigui; Naif Khalaf Alshammari; Makki Abdelmoleh (Green Chemistry Letters and Reviews)
The consumption of eggshell powder (ES) as an affluent source of calcium carbonate (CaCO3) can efficiently solve both ecological and financial interest. The use of eggshell waste in eco-composite materials (ECPCMs) is an attempt to reduce waste's negative effects. Eco-composite powders of polyethylene glycol (PEG) and calcium carbonate (CaCO3) were obtained by mechanical grinding. Compression molding was used to produce plates from the ground powders. FTIR spectroscopy and X-ray diffraction analysis showed that the ECPCMs were physically combined and the crystallinity of the two components was affected. According to TGA, the thermal stability of ECPCMs was improved, thanks to the use of eggshell waste powder. On the other hand, the results of the DSC showed that ECPCM with the addition of 90 wt% of PEG in the mixture provides excellent thermal stability and high energy storage density. In light of its high latent heat storage capacity of 156.1 J/g as well as its ability to prevent PEG exudation. Significant enhancement in melting-solidification time shows an improvement in Thermal Energy Storage (TES) response time by adding ES to the PCM. The obtained results indicate a good potential for industrially applied ECPCMs.